A material of easy-stretching aluminum foil and its preparation method and application
Patent Information
- Application Number
- CN202610982521.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-02
- Publication Date
- 2026-10-09
AI Technical Summary
然而,现有的铝箔材料存在明显的缺陷:单一铝箔结构的拉伸性能较差,在拉伸过程中容易出现破裂、撕裂等问题,导致产品的合格率降低;普通防护涂层的保护效果不佳,无法有效抵御外界环境的侵蚀,容易影响所包装物品的质量
1、本申请通过铝箔层中合金配比的优化,0.3%-0.5%的Si和0.3%-0.6%的Fe能在铝基体中形成细小、弥散的Al-Fe-Si第二相粒子,有效阻碍晶粒的长大,使得铝箔材料在拉伸变形时能够保持均匀延伸,再通过微量Ti的加入,能够显著细化铸态晶粒,使得拉伸变形在更多晶粒间均匀分布,再通过多层结构的复合设置,保护层能够在拉伸成型时起到润滑和缓冲的作用,内接触层则能够隔绝食品与铝箔层,满足食品接触安全需求,从而获得易拉伸的铝箔材料;
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This application relates to the field of aluminum foil processing, and in particular to a stretchable aluminum foil material, its preparation method, and its application. Background Technology
[0002] In the packaging materials industry, aluminum foil is widely used in numerous sectors, including food, pharmaceuticals, and electronics, due to its excellent barrier, light-blocking, and moisture-proof properties. With the continuous development of various industries, the performance requirements for aluminum foil materials are also increasing, especially in applications requiring stretching, such as the production of aluminum foil lunch boxes. In these cases, the tensile properties of aluminum foil are particularly important. Good tensile properties ensure that the aluminum foil is not easily broken during processing, thereby improving product quality and production efficiency.
[0003] In existing technologies, conventional methods to meet the basic performance requirements of aluminum foil materials mainly involve using a single aluminum foil structure or coating the aluminum foil surface with a common protective coating. However, existing aluminum foil materials have significant drawbacks: the tensile properties of a single aluminum foil structure are poor, making it prone to cracking and tearing during stretching, leading to a lower product yield; and the protective effect of common protective coatings is inadequate, failing to effectively resist external environmental corrosion and easily affecting the quality of packaged goods. Therefore, there is an urgent need for an aluminum foil material with ideal tensile properties. Summary of the Invention
[0004] To improve the stretchability of aluminum foil materials, this application provides an easily stretchable aluminum foil material, its preparation method, and its application.
[0005] Firstly, this application provides a stretchable aluminum foil material, which adopts the following technical solution: A stretchable aluminum foil material includes an aluminum foil layer, a protective layer coated on the bottom surface of the aluminum foil layer, and an inner contact layer coated on the top surface of the aluminum foil layer. The aluminum foil layer and the protective layer, as well as the aluminum foil layer and the inner contact layer, are connected by an adhesive. The aluminum foil layer comprises the following components in parts by weight: Si 0.3%-0.5%, Fe 0.3%-0.6%, Mn≤0.05%, Cu≤0.05%, Zn≤0.05%, Ti 0.01%-0.03%, single impurity element ≤0.03%, and the balance being Al; The aluminum foil layer has a thickness of 20-50 μm, the protective layer has a thickness of 5-10 μm, and the inner contact layer has a thickness of 3-8 μm.
[0006] By adopting the above technical solution and optimizing the alloy ratio in the aluminum foil layer, 0.3%-0.5% Si and 0.3%-0.6% Fe can form fine and dispersed Al-Fe-Si second-phase particles in the aluminum matrix, effectively hindering grain growth and enabling the aluminum foil material to maintain uniform elongation during stretching deformation. Furthermore, the addition of trace amounts of Ti can significantly refine the cast grains, allowing stretching deformation to be evenly distributed among more grains. Through the composite setting of multiple layers, the protective layer can play a lubricating and buffering role during stretching, while the inner contact layer can isolate food from the aluminum foil layer, meeting food contact safety requirements, thereby obtaining an easily stretchable aluminum foil material.
[0007] Preferably, the aluminum foil layer also contains Ce, and the amount of Ce added is 0.05%-0.2%.
[0008] By employing the above technical solution, the addition of trace amounts of Ce can form high-melting-point compounds with Al. During solidification, these compounds act as numerous heterogeneous nucleation sites, significantly refining the as-cast grains. In subsequent processing of the aluminum foil material, these high-melting-point compounds can pin grain boundaries, inhibiting the recrystallization and growth of fine grains. Furthermore, Ce has a strong affinity for hydrogen, reacting to generate stable rare-earth hydrides, which purify grain boundaries. These rare-earth hydrides are easily floated and skimmed off, greatly reducing the risk of hydrogen evolution and pinhole formation during solidification, resulting in a denser aluminum foil matrix.
[0009] Ce is a highly surface-active element that preferentially adsorbs onto the twin grooves and atomic steps where the β phase grows fastest, forming an atomic film that poisons the growth of the β phase, causing it to transform into granular or short rod-shaped particles. At the same time, it promotes the nucleation of the α phase, causing a large amount of fine α phase to precipitate preferentially in the melt. This transforms the brittle, flaky β phase in the as-cast structure into fine, rounded α phase particles, significantly improving the tensile properties of the aluminum foil material.
[0010] Preferably, the adhesive is an aliphatic two-component polyurethane adhesive.
[0011] Preferably, the main component of the aliphatic two-component polyurethane adhesive is a mixture of phosphate-modified epoxy resin and polyester polyol, and the curing agent is an aliphatic isocyanate.
[0012] By adopting the above technical solution, polyurethane itself has excellent elasticity with adjustable soft and hard segments, which allows the adhesive layer to deform along with the aluminum foil when the aluminum foil material is subjected to large deformation stretching such as deep drawing and folding.
[0013] By compounding phosphate-modified epoxy resin with polyester polyol to form the main component of aliphatic two-component polyurethane adhesive, the phosphate groups can form stable PO-Al chemical bonds with the hydroxyl groups on the aluminum foil surface, so that the adhesive layer can be firmly fixed on the aluminum foil layer when the aluminum foil material is stretched and deformed. At the same time, the presence of phosphate groups can also passivate the aluminum surface. The polyester polyol segments have good flexibility and can react with isocyanate to form highly elastic polyurethane segments.
[0014] The epoxy and hydroxyl groups in phosphate-modified epoxy resin and the hydroxyl groups in polyester polyol can react with the -NCO groups of aliphatic isocyanate to form an epoxy-polyurethane interpenetrating network. This allows the rigid network to provide shear strength and the flexible network to absorb deformation stress when the aluminum foil is stretched, ensuring that the stretched aluminum foil has ideal flatness.
[0015] When Ce is added to the system, the phosphate ester groups have a strong affinity for rare earth oxides, which can cause acid-base reactions or form stable Ce-OP covalent bonds, so that the aluminum foil material will not peel off in areas of severe deformation such as corners during extreme deep drawing.
[0016] Preferably, the mass ratio of the phosphate-modified epoxy resin to the polyester polyol is 10:90-15:85.
[0017] By adopting the above technical solution, when the amount of phosphate-modified epoxy resin added is too large, the flexible segments provided by the polyester polyol are diluted, which reduces the flexibility of the adhesive layer. During the stretching process of the aluminum foil material, the overly hard adhesive layer cannot be stretched synchronously. When the amount of phosphate-modified epoxy resin added is too small, the concentration of phosphate groups is too low, and a strong PO-Al chemical bonding network cannot be formed on the surface of the aluminum foil layer. This reduces the adhesion of the adhesive layer to the aluminum foil layer. Furthermore, if the epoxy resin component is too small, the strength of the adhesive layer itself is too low, and the adhesive layer is prone to internal tearing during the stretching process of the aluminum foil material.
[0018] Preferably, the protective layer is a nano-silica modified polyester film layer.
[0019] Preferably, the inner contact layer is a polyester film layer.
[0020] Secondly, this application provides a method for preparing an easily stretchable aluminum foil material, which adopts the following technical solution: A method for preparing an easily stretchable aluminum foil material includes the following steps: S1. The components of the aluminum foil layer are mixed and smelted according to the formula, and after degassing and slag removal, the aluminum foil is cast and rolled to obtain the cast and rolled billet. S2. The cast-rolled billet is subjected to homogenization annealing at 300-380℃ for 2-4 hours, then cooled to room temperature, and subjected to multiple cold rolling, intermediate annealing and finish rolling to obtain aluminum foil. S3. The bottom and top surfaces of the aluminum foil are subjected to low-temperature plasma activation treatment to obtain a surface-activated aluminum foil layer. Then, the surface-activated aluminum foil layer is immersed in a silane coupling agent and dried to obtain an aluminum foil layer. S4. After corona treatment, the protective layer is bonded to the bottom surface of the aluminum foil layer with an adhesive. Then, after corona treatment, the inner contact layer is bonded to the top surface of the aluminum foil layer with an adhesive. Finally, after curing, slitting and inspection, a stretchable aluminum foil material is obtained.
[0021] By adopting the above technical solutions, and through the coordinated design of aluminum foil alloy composition control and homogenization annealing, multi-pass cold rolling and intermediate annealing processes, the aluminum foil substrate is endowed with excellent elongation and flexibility, making it easy to stretch and deform without breaking during processing and use. At the same time, low-temperature plasma activation and silane coupling agent impregnation treatment construct a highly active chemical bonding layer on the aluminum foil surface, which greatly improves the interfacial bonding strength between the aluminum foil layer and the polyurethane adhesive, and forms a reliable composite structure with the corona-treated protective layer and inner contact layer, thereby obtaining an aluminum foil material with ideal performance.
[0022] Preferably, in S1, Ce is added in the form of an aluminum-cerium master alloy during the later stage of smelting and mixed with the aluminum foil layer components of the formula. After degassing and slag removal, the mixture is cast and rolled to obtain a cast-rolled billet.
[0023] By adopting the above technical solution, Ce is added to the system as an aluminum-cerium master alloy, which effectively reduces the probability of Ce being oxidized and burned off. Furthermore, the melting point of the aluminum-cerium master alloy is much lower than that of pure cerium, enabling it to melt quickly and diffuse evenly.
[0024] Thirdly, the aluminum foil lunch box provided in this application adopts the following technical solution: An aluminum foil lunch box is made from the aforementioned stretchable aluminum foil material.
[0025] In summary, this application includes at least one of the following beneficial technical effects: 1. This application optimizes the alloy ratio in the aluminum foil layer. 0.3%-0.5% Si and 0.3%-0.6% Fe can form fine and dispersed Al-Fe-Si second-phase particles in the aluminum matrix, which effectively hinders grain growth and allows the aluminum foil material to maintain uniform elongation during stretching deformation. Furthermore, the addition of trace amounts of Ti can significantly refine the cast grains, allowing the stretching deformation to be evenly distributed among more grains. Through the composite setting of multiple layers, the protective layer can play a lubricating and buffering role during stretching and forming, while the inner contact layer can isolate food from the aluminum foil layer, meeting the food contact safety requirements, thereby obtaining an easily stretchable aluminum foil material. 2. The addition of trace amounts of Ce in this application can form high-melting-point compounds with Al. During solidification, these compounds act as numerous heterogeneous nucleation sites, which can significantly refine the as-cast grains. In the subsequent processing of aluminum foil materials, these high-melting-point compounds can pin grain boundaries and inhibit the recrystallization and growth of fine grains. 3. This application uses phosphate-modified epoxy resin and polyester polyol to form the main component of an aliphatic two-component polyurethane adhesive. The phosphate groups can form stable PO-Al chemical bonds with the hydroxyl groups on the aluminum foil surface, so that the adhesive layer can be firmly fixed on the aluminum foil layer when the aluminum foil material is stretched and deformed. At the same time, the presence of phosphate groups can also passivate the aluminum surface. The polyester polyol segments have good flexibility and can react with isocyanate to form highly elastic polyurethane segments. Detailed Implementation
[0026] The raw materials in this application include the following: Polyester polyol: The commercially available product PL-2000 from Qingdao Ruinuo Chemical Co., Ltd. is used; Aliphatic isocyanate: The product with product number 7041107 from Shenzhen Dansong Plastics Co., Ltd. is used. Silane coupling agent: This application takes KH-550 with CAS number 919-30-2 as an example; Nano silica: Nano silica with a particle size of 50nm is used; Epoxy resin: Bisphenol A type epoxy resin with CAS number 25085-99-8 from Nanjing Zhongchun Biotechnology Co., Ltd. was used; Antioxidant: This application takes antioxidant 1010 with CAS number 6683-19-8 as an example; Lubricant: This application takes calcium stearate with CAS number 557-05-1 as an example.
[0027] Preparation Example 1 A method for preparing phosphate-modified epoxy resin includes the following steps: A1. Under a nitrogen atmosphere, heat 400g of epoxy resin to 90℃, add 0.8g of triethylamine, and stir until dissolved to obtain a mixture. A2. Slowly add 50g of phosphoric acid to the mixture, then heat to 110℃ and keep warm for 3 hours. After the epoxy value drops to 0, cool down to 60℃, add 200mL of ethyl acetate and stir for 20 minutes to obtain phosphoric acid modified epoxy resin.
[0028] Preparation Example 2 A method for preparing a nano-silica modified polyester film layer includes the following steps: B1. Mix silane coupling agent with deionized water and anhydrous ethanol in a mass ratio of 1:1:8, adjust the pH to 4-5 with glacial acetic acid, and stir and hydrolyze at 30°C for 45 min to obtain silane coupling agent hydrolysate. B2. Mix nano-silica with silane coupling agent hydrolysate at a mass ratio of 10:1, stir and react at 70°C for 3 hours, centrifuge and wash three times with anhydrous ethanol, and vacuum dry at 90°C for 5 hours to obtain modified nano-silica. B3. After mixing modified nano-silica, dispersant and a small amount of PET for 15 minutes, the mixture is fed into a twin-screw extruder. The screw speed is 300 rpm, and the extruder temperature is 260℃ in zone 1, 270℃ in zone 2, 275℃ in zone 3, 280℃ in zone 4 and 275℃ in zone 5 to obtain masterbatch. The amount of PET added is 5% of the total PET mass. B4. Dry the masterbatch at 130℃ for 5 hours. Mix the masterbatch with PET chips, antioxidants, and lubricants, and then put it into an extruder for melt extrusion at 280℃. After extrusion, quickly cool and shape it on a cooling roller at 280℃, 1mm die lip gap, and 25℃ to obtain a cast sheet. The amount of masterbatch added is 20%. B5. The casting sheet is stretched longitudinally and transversely, with a longitudinal stretching ratio of 4 times and a transverse stretching ratio of 4 times. After cooling and trimming, a nano-silica modified polyester film layer is obtained.
[0029] The present application will be further described in detail below with reference to embodiments and comparative examples.
[0030] Example 1
[0031] A method for preparing an easily stretchable aluminum foil material includes the following steps: S1. The components of the aluminum foil layer are mixed according to the formula and melted at 750℃. High-purity argon gas is introduced for rotary blowing degassing for 20 minutes at a flow rate of 2.0L / min. Then, the slag is removed online by passing it through a 30ppi ceramic foam filter plate. Semi-continuous casting and rolling is carried out at 700℃ to obtain the cast and rolled billet. S2. The cast-rolled billet is subjected to homogenization annealing at 350℃ for 3 hours, then cooled to room temperature at a rate of 20℃ / h, and then subjected to multi-pass cold rolling, intermediate annealing at 300℃ for 2 hours, and finish rolling to obtain an aluminum foil with a thickness of 35μm. S3. Place an aluminum foil with a thickness of 35μm into an RF plasma treatment chamber. Under an air atmosphere, the aluminum foil substrate temperature is 30℃, the RF power is 400W, the treatment pressure is 30Pa, and the treatment time is 90s. Perform low-temperature plasma activation treatment on the top and bottom surfaces of the aluminum foil to obtain a surface-activated aluminum foil layer. Use ethanol and water at a volume ratio of 95:5 as a solvent to prepare a silane coupling agent solution with a silane mass concentration of 1.5%. Then immerse the surface-activated aluminum foil layer in the silane coupling agent solution for 8min, take it out and dry it at 110℃ for 12min to obtain the aluminum foil layer. S4. After corona treatment, a 7μm thick protective layer is hot-pressed onto the bottom surface of the aluminum foil layer using an adhesive and a composite roller. The composite temperature is 75℃ and the composite pressure is 0.5MPa. Then, after corona treatment, a 5μm thick inner contact layer is hot-pressed onto the top surface of the aluminum foil layer using an adhesive and a composite roller. The composite temperature is 75℃ and the composite pressure is 0.5MPa. Finally, after curing at 50℃ for 72 hours, slitting, and inspection, easily stretchable aluminum foil material is obtained. The corona treatment conditions are a power of 1.5kW and a processing speed of 30m / min.
[0032] The aluminum foil layer comprises the following components by weight: Si 0.3%-0.5%, Fe 0.3%-0.6%, Mn≤0.05%, Cu≤0.05%, Zn≤0.05%, Ti 0.01%-0.03%, single impurity element ≤0.03%, and the balance being Al. The adhesive is an aliphatic two-component polyurethane adhesive, the main component of which is a mixture of phosphate-modified epoxy resin and polyester polyol, and the curing agent is an aliphatic isocyanate. The mass ratio of the main component to the curing agent is 100:12, and the mass ratio of the phosphate-modified epoxy resin to the polyester polyol is 13:87. The protective layer is the nano-silica-modified polyester film layer obtained in Preparation Example 2, and the inner contact layer is a polyester film layer.
[0033] Comparative Example 1 Comparative Example 1 adjusts the composition of the aluminum foil layer based on the preparation method of Example 1, as shown in Table 1.
[0034] Performance testing The stretchable aluminum foil materials of Example 1 and Comparative Example 1 were analyzed, and the specific testing methods are as follows: 1. Mechanical properties The tensile strength, yield strength, and elongation of aluminum foil materials were tested according to the standard testing methods specified in GB / T 228.1-2010.
[0035] Based on the above detection method, the test results of Example 1 and Comparative Example 1 were obtained, as shown in Table 1 below.
[0036] Table 1. Weight ratio of aluminum foil layer components and their performance test results for Example 1 and Comparative Example 1.
[0037] Referring to Table 1, it can be seen from the comparison between Example 1 and Comparative Example 1 that the addition of Ti can significantly improve the tensile properties of aluminum foil materials. This is because Ti can significantly refine the cast grains, so that the tensile deformation is evenly distributed among more grains.
[0038] Example 2-3 Based on the preparation method of Example 1, Examples 2-3 adjust the thickness of the aluminum foil layer, protective layer and inner contact layer, as shown in Table 2.
[0039] Comparative Examples 2-3 Comparative Examples 2-3 are based on the preparation method of Example 1, but the thicknesses of the aluminum foil layer, protective layer and inner contact layer are adjusted as shown in Table 2.
[0040] The stretchable aluminum foil materials of Examples 2-3 and Comparative Examples 2-3 were subjected to the above-mentioned performance tests, and the test results are shown in Table 2.
[0041] Table 2. Thickness and performance test results of aluminum foil layer, protective layer and inner contact layer in Examples 1-3 and Comparative Examples 2-3.
[0042] Referring to Table 2, comparing Examples 1-3 and Comparative Examples 2-3, it can be seen that when the thickness of the aluminum foil layer is in the range of 20-50 μm, the thickness of the protective layer is in the range of 5-10 μm, and the thickness of the inner contact layer is in the range of 3-8 μm, the performance of the obtained aluminum foil material is optimal.
[0043] Example 4 Example 4 is based on the preparation method of Example 1. In S1, aluminum-cerium master alloy is added in the later stage of melting and mixed with other components of aluminum foil layer for melting. After degassing and slag removal, cast-rolled billet is obtained. The other conditions remain unchanged. The weight percentage of cerium in aluminum foil layer components is 0.12%.
[0044] Examples 5-8 Examples 5-8 are based on the preparation method of Example 4, but the weight percentage of cerium in the aluminum foil layer components is adjusted, as shown in Table 3.
[0045] The stretchable aluminum foil materials of Examples 4-8 were subjected to the above-mentioned performance tests, and the test results are shown in Table 3.
[0046] Table 3. Weight percentage of cerium in the aluminum foil layer composition and its performance test results in Examples 1 and 4-8.
[0047] Referring to Table 3, it can be seen from the comparison between Example 1 and Examples 4-8 that the addition of Ce can significantly improve the performance of aluminum foil materials. This is because the addition of Ce can form high-melting-point compounds with Al. During the solidification process, Ce acts as a large number of heterogeneous nucleation cores, which can significantly refine the cast grains. In the subsequent processing of aluminum foil materials, the above-mentioned high-melting-point compounds can pin the grain boundaries and inhibit the recrystallization and growth of fine grains.
[0048] Example 9 Example 9 is based on the preparation method of Example 4, but the main component of the aliphatic two-component polyurethane adhesive is adjusted, as shown in Table 4.
[0049] Performance testing The stretchable aluminum foil materials from Examples 4 and 9 were analyzed using the following specific testing methods: 1. Adhesion According to the standard testing method specified in GB / T 9286-1998, a 6×6 grid (2mm spacing) is cut on the surface of the adhesive layer with a blade, the cutting depth is to the aluminum foil layer, 3M transparent tape (18mm wide) is pressed to the grid area, and then quickly peeled off at a 90° angle. The coating peeling ratio is observed under a microscope and rated on a scale of 0-5, with 0 indicating no peeling.
[0050] Based on the above detection method, the test results of Examples 4 and 9 were obtained, as shown in Table 1 below.
[0051] Table 4 Performance test results for Examples 4 and 9
[0052] Referring to Table 4, a comparison of Examples 4 and 9 shows that by compounding phosphate-modified epoxy resin with polyester polyol to form the main component of an aliphatic two-component polyurethane adhesive, the phosphate groups can form stable PO-Al chemical bonds with the hydroxyl groups on the aluminum foil surface, so that the adhesive layer can be firmly fixed on the aluminum foil layer when the aluminum foil material is stretched and deformed. At the same time, the presence of phosphate groups can also passivate the aluminum surface. The polyester polyol segments have good flexibility and can react with isocyanate to form highly elastic polyurethane segments, thereby obtaining an aluminum foil material with ideal performance.
[0053] Examples 10-13 Examples 10-13 are based on the preparation method of Example 4, but the mass ratio of phosphate-modified epoxy resin to polyester polyol is adjusted as shown in Table 5.
[0054] Table 5. Mass ratio of phosphate-modified epoxy resin to polyester polyol and its performance test results in Examples 4 and 10-13.
[0055] Referring to Table 5, a comparison of Examples 4 and 10-13 shows that the aluminum foil material with the best performance is obtained when the mass ratio of phosphate-modified epoxy resin to polyester polyol is in the range of 10:90-15:85.
[0056] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A stretchable aluminum foil material, characterized in that, It includes an aluminum foil layer, a protective layer coated on the bottom surface of the aluminum foil layer, and an inner contact layer coated on the top surface of the aluminum foil layer. The aluminum foil layer and the protective layer, as well as the aluminum foil layer and the inner contact layer, are connected by an adhesive. The aluminum foil layer comprises the following components in parts by weight: Si 0.3%-0.5%, Fe 0.3%-0.6%, Mn≤0.05%, Cu≤0.05%, Zn≤0.05%, Ti 0.01%-0.03%, single impurity element ≤0.03%, and the balance being Al; The aluminum foil layer has a thickness of 20-50 μm, the protective layer has a thickness of 5-10 μm, and the inner contact layer has a thickness of 3-8 μm.
2. The easily stretchable aluminum foil material according to claim 1, characterized in that, The aluminum foil layer also contains Ce, with the amount of Ce added being 0.05%-0.2%.
3. The easily stretchable aluminum foil material according to claim 2, characterized in that, The adhesive is an aliphatic two-component polyurethane adhesive.
4. The easily stretchable aluminum foil material according to claim 3, characterized in that, The main component of the aliphatic two-component polyurethane adhesive is a mixture of phosphate-modified epoxy resin and polyester polyol, and the curing agent is aliphatic isocyanate.
5. The easily stretchable aluminum foil material according to claim 4, characterized in that, The mass ratio of the phosphate-modified epoxy resin to the polyester polyol is 10:90-15:
85.
6. The easily stretchable aluminum foil material according to claim 1, characterized in that, The protective layer is a nano-silica modified polyester film layer.
7. The easily stretchable aluminum foil material according to claim 1, characterized in that, The inner contact layer is a polyester film layer.
8. A method for preparing an easily stretchable aluminum foil material according to any one of claims 1-7, characterized in that, Includes the following steps: S1. The components of the aluminum foil layer are mixed and smelted according to the formula, and after degassing and slag removal, the aluminum foil is cast and rolled to obtain the cast and rolled billet. S2. The cast-rolled billet is subjected to homogenization annealing at 300-380℃ for 2-4 hours, then cooled to room temperature, and subjected to multiple cold rolling, intermediate annealing and finish rolling to obtain aluminum foil. S3. The bottom and top surfaces of the aluminum foil are subjected to low-temperature plasma activation treatment to obtain a surface-activated aluminum foil layer. Then, the surface-activated aluminum foil layer is immersed in a silane coupling agent and dried to obtain an aluminum foil layer. S4. After corona treatment, the protective layer is bonded to the bottom surface of the aluminum foil layer with an adhesive. Then, after corona treatment, the inner contact layer is bonded to the top surface of the aluminum foil layer with an adhesive. Finally, after curing, slitting and inspection, a stretchable aluminum foil material is obtained.
9. The method for preparing an easily stretchable aluminum foil material according to claim 8, characterized in that, In S1, Ce is added in the late stage of smelting as an aluminum-cerium master alloy and mixed with the aluminum foil layer components of the formula. After degassing and slag removal, the mixture is cast and rolled to obtain a cast-rolled billet.
10. An aluminum foil lunch box, characterized in that, It is made from a stretchable aluminum foil material as described in any one of claims 1-7.